Preparation and characterization of novel thermoset polyimide and polyimide-peo doped with LiCF3SO3 - KAYAMAN APOHAN, NİLHAN (BUDAPEST UNIV TECHNOL & ECON, 2014)
This paper deals with the synthesis and characterization of a new type of anhydrous ionic conducting lithium doped membranes consist of polyimide (PI), poly (ethylene oxide) (PEO) and lithium trifluoromethanesulfonate (LiCF3SO3) for solid polymer electrolyte (SPE). For this purpose, different molar ratios of lithium salt (Li-salt) solution are added into poly (amic acid) (PAA) intermediate prepared from the reaction of 3,3',4,4'-benzophenon tetracarboxylic dianhydride (BTDA) and 4,4'-oxydianiline (ODA). PEO is incorporated into PAA since it forms more stable complexes and possess high ionic conductivities. Then, Li-salt containing PAA solutions are imidized by thermal process. The effect of interaction between host polymer and Li-salt is characterized by FT-IR (Fourier Transform Infrared) spectroscopy and SEM (scanning electron micrsocopy). The conductivities of Li-salt and PEO containing PI composite membranes are in the range of 10(-7)-10(-5) S center dot cm(-1). The conductivity increases with incorporation of PEO. Thermogravimetric analysis results reveal that the PI/PEO/LiCF3SO3 composite polymer electrolyte membranes are thermally stable up to 500 degrees C.
Keywords: polymer composites; polymer membranes; ionic conductivity; LITHIUM-ION BATTERIES; ALKALI-METAL SALTS; POLYMER ELECTROLYTES; ELECTROCHEMICAL PROPERTIES; POLY(ETHYLENE OXIDE); SOLID ELECTROLYTES; CONDUCTIVITY; TRANSPORT; COPOLYMERS